Defining alternatives in the context of education - Sierra Salcedo, Regla Alicia; Imbert Stable, Neris (Transformación, 2024)
Objective: The study aims at conceptualizing the different types of alternatives faced at educational institutions.Methods: The systematization of previous authors’ scientific findings was used. Authoresses rely not only on their experience in psychologist and teacher training but on records of teaching activities and teaching planning sections.Results: The general conceptualization of alternative is offered, its main types are identified and the relation of each type of alternative to their respective goals, context, processes and subjects is illustrated.   Conclusion: The pedagogical alternative, in its close relationship with the strategy of the same nature, constitutes a way of solving problems in the school context.
Keywords: educational strategy; teaching method; teaching procedures; educational planning